Analysis of Perception and Behaviour in Choosing Halal Labels Related to Food, Pharmacy and Cosmetics at the Regional Office of the Ministry of Religion - Hakim, Muhammad Luqman (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2021)
This is a field research to highlight the issue of halal lifestyle in East Java Regional Office employees. This problem will be broken down into two basic problems, namely; firstly how is the halal lifestyle perception related to food, pharmacy and cosmetics among employees in the Ministry of Religion of East Java Province, and second how is the halal lifestyle behavior related to food, pharmacy and cosmetics to employees in the Ministry of Religion of East Java Province. Data obtained through questionnaires to respondents with purposive sampling technique. The analytical method in this study uses multiple linear regression analysis and linkert scale. The results of this study indicate that halal food, halal pharmacy and halal cosmetics simultaneously have a significant influence on Halal Lifestyle of East Java Regional Office of Ministry of Religion.